An?lise dos principais efeitos da propaga??o de sinais ?pticos, no espa?o livre, revestida de uma plataforma num?rica eficiente - Coura, Daniel Jos? Cust?dio (2004)
This dissertation presents the keys elements of an optical link in the free space. At first, we realize an analysis of the link through the vacuum and later a complementary study is done related with the effect caused by the atmosphere in the propagation. Throughout this work it is demonstrated how to get the main parameters and the propagation modes of the Gaussian beam, as well as the performance of the beam expanders inside the reach of the optical link. This study also treats the effect caused for the propagation in the atmosphere, which are divided in the atmospheric attenuation and the variation of the refraction index. The study will permit to present a set of original computational programs, which are elaborated during the preparation of this dissertation and it serves as a tool to visualize the theoretical topics, as well as to give a great contribution in the analysis of the fundamental parameters in the optical link. All the visual programs had been generated using the computer programming Matlab and C++ Builder.